Impact Analysis of Cluster Frontline Demonstrations on Groundnut in Nalgonda District, Telangana - Marlabeedu, Shankar; Bharath, Tejavath; Pallavi, Surapaka; Himabindu, Tanguturi; Shankaraiah, Mekala; Sumalini, Katragadda (Indian Journal of Extension Education, 2022)
The present study was conducted to analyze the yield gap between improved package of practices and farmers’ practice during rabi 2016-17 to 2020-21 in CFLDs on groundnut. The highest average pod yield was obtained in CFLDs (2341.6 kg/ha), with 27 per cent more against farmers’ practice (1843.6 kg/ha). The average extension gap, technology gap and technology index were 498.0 kg/ha, 658.4 kg/ha and 21.9 per cent, respectively. Sustainability yield index (0.78) and sustainability value index (0.84) averages were high in improved practice over the farmers’ practice (0.76 and 0.75). The average gross returns (Rs. 1,28,283.0/ha), net returns (Rs. 71,934.0/ha) and benefit-cost ratio (2.6) were higher in improved practice when compared to farmers’ practice. The mean of additional gross returns (Rs. 24,873.0/ha), cost of cultivation (Rs. 4,151.0/ha), net returns (Rs. 28,402.0/ ha) with incremental benefit-cost ratio of 6.0 was observed in improved practice. The average yield gap percentages within district and state averages were 64.2 per cent and 45.6 per cent, respectively. The per cent increased horizontal spread of area under groundnut was 14.1 per cent, 23.9 per cent and 27.5 per cent during study period, whereas in 2016-17 and 2018-19 per cent horizontal spread area decreased -52.3 per cent and -15.9 per cent, respectively with cultivation of improved varieties i.e., K-9 and ICGV 3043 against cultivation of old traditional varieties.
Keywords: Groundnut; CFLD; Yield; Sustainability yield index; Sustainability value index; Economics